Ricardo Sternberg and "This Dreamt Departure to EL Dorado, The Indians, The Island of Hy-Breasil" - Maria Lúcia Milléo Martins (Ilha do Desterro)
Ricardo Sternberg and "This Dreamt Departure to EL Dorado, The Indians, The Island of Hy-Breasil"